VIS/NIR hyperspectral imaging and N-way PLS-DA models for detection of decay lesions in citrus fruits - Folch-Fortuny, A.; Prats-Montalbán, José M.; Cubero, Sergio; Blasco, José; Ferrer, Alberto (Elsevier, 2020)
In this work an N-way partial least squares regression discriminant analysis (NPLS-DA) methodology is developed to detect symptoms of disease caused by Penicillium digitatum in citrus fruits (green mould) using visible/near infrared (VIS/NIR) hyperspectral images. To build the discriminant model a set of oranges and mandarins was infected by the fungus and another set was infiltrated just with water for control purposes. A double cross-validation strategy is used to validate the discriminant models. Finally, permutation testing is used to select a few bands offering the best correct classification rates in the validation set. The discriminant models developed here can be potentially implemented in a fruit packinghouse to detect infected citrus fruits at their arrival from the field with affordable multispectral (3–5 channels) cameras installed in the packinglines.